Historical matters in medical publications of the turn of the XIX-XX centuries - M. S. Tutorskaya (Кардиоваскулярная терапия и профилактика)
This paper analyses different approaches to historical and medical matters at the turn of the 19th-20th centuries: the methods of lecturers at the Medical Faculty of the Imperial Moscow University and the humanities course that was developed for medical students at the Imperial Military Medical Academy in St. Petersburg. Examples of the so-called "corporate" history of medicine - historical essays and anniversary publications prepared by medical societies and medical institutions - are given; the aims and objectives of such publications and the formation of the genre as a whole are considered. Along with the history of medicine for future and already practicing doctors at the turn of the 19th and 20th centuries, historical subjects also appeared in the literature on health for the people. Popularizing medical knowledge, the authors of pamphlets familiarized the public reader not only with the rules of hygiene and the basics of patient care, but also with doctors and their discoveries.